ELECTRIC WASTE PROCESSING IN BRAZIL - da Paixão, Carlos Henrique; Oliveira , André Luiz (Revista Interface Tecnológica, 2023)
This research aimed to analyze the management of Electrical and Electronic Equipment Waste (EEEW) in Brazil, identifying the challenges and positive initiatives in this area. The methodology used was a literature review of articles and legislation related to the topic, as well as the analysis of available statistical data. The results showed that the EEEW production chain in Brazil is still incipient, lacking better integration between the different links in the chain and the creation of mechanisms to ensure producer responsibility for the life cycle of their products. In addition, reverse logistics is still a challenge, both in terms of structuring and raising awareness among consumers. However, there are positive initiatives underway, such as the creation of selective EEEW collection systems in some cities and awareness-raising actions among the population. Based on these results, it is concluded that greater coordination is necessary among the different actors involved in EEEW management, as well as the development of strategies to encourage the implementation of effective reverse logistics systems.